Quintuple band antenna design using stacked series array for millimeter wave - Nibir, Rauful; Islam, Md. Rafiqul; Nafi, Nazmus Shaker; Gregory, Mark A. (IEEE, 2020)
Millimeter wave applications require efficient array antenna designs to fully utilize the spectrum. A quintuple band antenna is proposed for millimeter wave applications. Dual-layer substrate technology is utilized to achieve multiple resonances at higher frequencies ranging from 26GHz-40GHz. Twenty-five antenna array configurations were simulated and analyzed to develop the model. The resonances achieved correspond to the number of radiating patches. The operating frequencies of this design correspond with single band 27.64 GHz, dual band 24.18, 28.77 GHz, triple band resonances 23.18, 25.63, 35.79 GHz, quadruple band resonances 24.58, 26.77, 29.33, 34.43 GHz and quintuple band resonances 23.79, 25.37, 28.29, 31.69, 33.53 GHz. The proposed quintuple band antenna can be used for millimeter wave applications in all bands.